2009
DOI: 10.1029/2009gl038156
|View full text |Cite
|
Sign up to set email alerts
|

First simultaneous observations of daytime MSTIDs over North America using GPS‐TEC and DEMETER satellite data

Abstract: [1] We present simultaneous observations of daytime medium-scale traveling ionospheric disturbances (MSTIDs) over North America, using measurements of the Total Electron Content (TEC) by the US GPS network and ionospheric plasma data from the DEMETER microsatellite. Several events show latitudinal variations of the plasma parameters at satellite altitude corresponding to the MSTID structures revealed on 2D TEC maps. In a case study with a very well defined MSTID, quasi periodic variations of the plasma density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 15 publications
3
14
0
Order By: Relevance
“…In addition, Jhuang et al (2010) found a middle latitude enhancement in DEME-TER ISL data in the nighttime from September to April during 2005 -2009, consistent with the ionospheric F2 region observation detected with ionosonde, incoherent scatter radar and the techniques for GPS total electron content (TEC) (Jhuang et al 2010). Onishi et al (2009) studied the MSTIDs using GPS TEC, which was also detected in the parallel plasma motion observation on DEMETER. Zhao et al (2013) combined the NmF2 and N e data from ionosonde stations, COSMIC RO and DEMETER to study the east -west differences in the F-region over the Far East region, with some new features revealed for understanding the ionospheric longitude difference at mid-latitude.…”
Section: Demeter Satellitesupporting
confidence: 61%
See 1 more Smart Citation
“…In addition, Jhuang et al (2010) found a middle latitude enhancement in DEME-TER ISL data in the nighttime from September to April during 2005 -2009, consistent with the ionospheric F2 region observation detected with ionosonde, incoherent scatter radar and the techniques for GPS total electron content (TEC) (Jhuang et al 2010). Onishi et al (2009) studied the MSTIDs using GPS TEC, which was also detected in the parallel plasma motion observation on DEMETER. Zhao et al (2013) combined the NmF2 and N e data from ionosonde stations, COSMIC RO and DEMETER to study the east -west differences in the F-region over the Far East region, with some new features revealed for understanding the ionospheric longitude difference at mid-latitude.…”
Section: Demeter Satellitesupporting
confidence: 61%
“…The plasma parameters detected by the ISL have been used in many papers (Onishi et al 2009;Jhuang et al 2010;Kakinami et al 2011;Li et al 2011;Zhao et al 2013). Kakinami et al (2011) studied the daytime longitudinal structures of electron density and temperature in the topside ionosphere observed by the Hinotori and DEMETER satellites, which showed a similar longitudinal N e structure in the morning from July to October, and similar pronounced N e maxima in Southeast Asia, the Pacific Ocean and west of South America in the different solar flux conditions.…”
Section: Demeter Satellitementioning
confidence: 99%
“…Occurrence of LSTIDs is generally related to geomagnetic activity, and they travel from the polar regions toward the equator, while MSTIDs are typically observed at midlatitudes during both quiet and disturbed conditions. Further, MSTID and LSTID characteristics were investigated using dense GPS receiver networks in Japan [e.g., Saito et al, 2001;Shiokawa et al, 2002;Tsugawa et al, 2003;Tsugawa and Saito, 2004;Nishioka et al, 2009;Hayashi et al, 2010], North America [e.g., Nicolls et al, 2004;Tsugawa et al, 2007;Kotake et al, 2007;Onishi et al, 2009], and less dense GPS networks in Europe [Borries et al, 2009;Jakowski et al, 2012;Otsuka et al, 2013] and China [Song et al, 2013;Ding et al, 2014]. Since mid-1990s, ground-based segment of the Global Positioning System (GPS) started to grow up extensively from several hundred stations worldwide to more than 6000 stations today.…”
Section: Introductionmentioning
confidence: 99%
“…Since these initial observations, the characteristics of TIDs have been investigated using a variety of techniques. These include (a) electron density measurements using vertical and oblique ionosondes (e.g., Afraimovich et al, ; Morgan et al, ; Ogawa et al, ; Tedd et al, ) and incoherent scatter radars (ISRs; e.g., Djuth et al, , ; Fukao et al, ; Nicolls & Heinselman, ), (b) backscatter radar soundings (e.g., Bristow et al, ; Bristow & Greenwald, ; Frissell et al, , ), (c) continuous wave (CW) Doppler measurements (e.g., Georges, ; Hung et al, ; Röttger, ), (d) total electron content (TEC) measurements using Global Positioning System (GPS) satellite constellations (e.g., Galushko et al, ; Nicolls et al, ; Onishi et al, ), and (e) optical airglow measurements (e.g., Kubota et al, ; Paulino et al, ; Shiokawa et al, , ). All of these measurement techniques have their strengths and limitations.…”
Section: Introductionmentioning
confidence: 99%